ENGARUH TAX PLANNING DAN GREEN INNOVATION TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI PEMEDIASI - , Nurul Badriyah, Nazivah Arini , Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Company value is the company's performance which is reflected in the stock price which reflects society's assessment of company performance (Cholifah & Kaharti, 2021). This study aims to examine and analyze the effect of tax planning and green innovation on company value with profitability as a mediating variable in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2021. The data used in this study is secondary data obtained from the annual financial reports of companies in the consumer goods industry sector. The population in this study are all manufacturing companies in the consumer goods industry sector, totaling 59 companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique was purposive sampling so 30 companies were included in the criteria. The data analysis technique used multiple linear regression analysis and path analysis using SPSS (Statistical Product and Service Solutions) version 23. This study found that tax planning does not affect firm value. Green innovation and profitability affect company value. Tax planning affects profitability by proxy for ROA. Green innovation does not affect profitability. Tax planning has no significant effect on firm value which is mediated by profitability. Meanwhile, green innovation has a significant influence on company value which is mediated by profitability. Keywords: Tax Planning, Green Innovation, Firm Value, Profitability